Compartmentalized cAMP/PKA signalling regulates cardiac excitation-contraction coupling. - Lissandron, V; Zaccolo, M (2006)
The sympathetic control over excitation-contraction coupling (ECC) is mediated by the cAMP/PKA signalling pathway. However, in the myocyte, the same signalling pathway is responsible for triggering a plethora of diverse intracellular functions the control of which must be independent of the regulation of ECC. Here we discuss what are the molecular mechanisms leading to selective modulation of ECC in cardiac myocytes with a particular focus on the role of spatial confinement of PKA subsets and the compartmentalization of cAMP.